C4 plants use fluctuating light less efficiently than do C3 plants: a study of growth, photosynthesis and carbon isotope discrimination - Kubásek, Jiří; Urban, Otmar; Šantrůček, Jiří (Physiologia plantarum, 2013)
Plants in the field are commonly exposed to fluctuating light intensity, caused by variable cloud cover, self-shading of leaves in the canopy and/or leaf movement due to turbulence. In contrast to C3 plant species, only little is known about the effects of dynamic light (DL) on photosynthesis and growth in C4 plants. Two C4 and two C3 monocot and eudicot species were grown under steady light or DL conditions with equal sum of daily incident photon flux. We measured leaf gas exchange, plant growth and dry matter carbon isotope discrimination to infer CO2 bundle sheath leakiness in C4 plants. The growth of all species was reduced by DL, despite only small changes in steady-state gas exchange characteristics, and this effect was more pronounced in C4 than C3 species due to lower assimilation at light transitions. This was partially attributed to increased bundle sheath leakiness in C4 plants under the simulated lightfleck conditions. We hypothesize that DL leads to imbalances in the coordination of C4 and C3 cycles and increasing leakiness, thereby decreasing the quantum efficiency of photosynthesis. In addition to their other constraints, the inability of C4 plants to efficiently utilize fluctuating light likely contributes to their absence in such environments as forest understoreys.
Keywords: transpirace rostlin; Photosynthesis; Carbon Isotopes; lipnicovité; fotosyntéza; listy rostlin; Plant Transpiration; Light; Amaranthaceae; Poaceae; světlo; Plant Leaves; Carbon Dioxide; oxid uhličitý; Photons; izotopy uhlíku; fotony